2018
DOI: 10.1007/s11356-018-1665-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between urinary cadmium and chronic musculoskeletal pain in residents of cadmium-contaminated area in Northwest Thailand

Abstract: Cadmium exposure is known to cause adverse health effects in different organs of the human body but whether the effects result in chronic musculoskeletal pain (CMP) remain inclusive. The present study, therefore, aims to examine the relationship between urinary cadmium levels and CMP. An observational retrospective cohort study was conducted in two areas having different levels of cadmium contamination for comparison. The subjects enrolled into the study were individuals ages 18 and above who have lived in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The survey showed that for the cadmium-contaminated areas in northwest Thailand, people had high risk of being trapped in chronic musculoskeletal pain. This finding in turn suggests that exposure to cadmium, which is contained in EC vaping, may cause chronic musculoskeletal pain [34].…”
Section: Compounds and Potential Painsmentioning
confidence: 98%
See 1 more Smart Citation
“…The survey showed that for the cadmium-contaminated areas in northwest Thailand, people had high risk of being trapped in chronic musculoskeletal pain. This finding in turn suggests that exposure to cadmium, which is contained in EC vaping, may cause chronic musculoskeletal pain [34].…”
Section: Compounds and Potential Painsmentioning
confidence: 98%
“…Meanwhile, propylene glycol could attenuate the adverse effects of high-dose nicotine and allow EC users to develop high tolerance toward EC products [33]. By analyzing urinary cadmium levels, La-Up et al [34] found there was a positive relationship between urinary cadmium level and chronic musculoskeletal pain. The survey showed that for the cadmium-contaminated areas in northwest Thailand, people had high risk of being trapped in chronic musculoskeletal pain.…”
Section: Compounds and Potential Painsmentioning
confidence: 99%
“…La-Up et al found a positive association between urinary Cd concentrations and chronic musculoskeletal pain, suggesting that Cd exposure may cause neurological damage or damage to musculoskeletal tissue, resulting in chronic pain. In addition, Cd induces oxidative stress, which is associated with chronic muscular pain [ 46 ]. Ibrahim et al also confirmed a positive correlation between the increased incidence of musculoskeletal complaints, bone pain, joint pain and muscle spasms and Cd levels in the blood and urine among Cd-exposed workers compared to a control group [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to environmental cadmium poses many public health problems, as it is a highly toxic substance that can cause important adverse health effects [33][34][35]. At high doses, cadmium is known to cause the so-called itai-itai disease whose dominant symptom is back pain [36].…”
Section: Plos Onementioning
confidence: 99%